Pengaruh Promosi dan Kemudahan Terhadap Keputusan Penggunaan Dompet Digital Shopeepay Pada Mahasiswa Institut Stiami Bekasi A Angkatan 2019 - Krishantoro, Krishantoro; Nisa, Toifatun (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to investigate the factors influencing the decision of STIAMI Institute students in Bekasi A to use the ShopeePay digital wallet for online shopping activities. In an era of rapid technological development, human shopping activities are increasingly facilitated by the presence of digital wallet applications. The focus of this research is on promotion and ease of access as two main variables that may affect students' decisions in choosing ShopeePay. Based on survey data conducted, ShopeePay emerges as one of the most preferred digital wallets among STIAMI students. Research results indicate that ShopeePay's vigorous promotions, such as free shipping and special discounts, have successfully attracted students' interest. Additionally, ease of transaction process and ShopeePay balance top-up also play crucial roles in influencing usage decisions. Although some previous studies have shown results consistent with these findings, there are differences to be noted. A previous study found that ease of access is not significant in influencing students' decisions. This may suggest that students who are accustomed to technology tend to focus more on promotional factors. In conclusion, promotion and ease of access are two significant factors influencing students' decisions to use ShopeePay for online shopping activities. The findings of this research can provide valuable insights for e-commerce companies and digital wallet providers to enhance promotion strategies and ensure ease of access for usage, especially in the context of students.